2017
DOI: 10.20874/2071-0437-2017-39-4-195-204
|View full text |Cite
|
Sign up to set email alerts
|

Agricultue in Southern Primorye in the I Millennium Bc According to Archaeobotanical Data From the Settlement of Cherepakha-13

Abstract: ЗЕМЛЕДЕЛИЕ В ЮЖНОМ ПРИМОРЬЕ В I тыс. до н.э.: КАРПОЛОГИЧЕСКИЕ МАТЕРИАЛЫ ПОСЕЛЕНИЯ ЧЕРЕПАХА-13Коллекция карбонизированных семян растений из заполнений жилищ янковской (2800-2000 л.н.) и кроуновской (2500-1900 л.н.) Ключевые слова: земледелие, флотация, семена, итальянское, обыкновенное и японское просо, ячмень, соя, ранний железный век, I тыс. до н.э., юг Дальнего Востока России. DOI: 10.20874/2071DOI: 10.20874/ -0437-2017 Введение Роль земледелия в системах жизнеобеспечения населения юга Дальнего Востока Ро… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 1 publication
0
1
0
Order By: Relevance
“…It is suggested that when the Cherepakha 13 site was occupied by the YC population, the level of the Sea of Japan dropped, and this may have caused a decrease of marine resources (Razjigaeva et al 2017a). Archaeobotanical research at the Cherepakha 13 site (Sergusheva and Moreva 2017) allowed us to identify the seeds of two species of millet: broomcorn millet ( Panicum miliaceum ) and foxtail millet ( Setaria italica ) in the YC layer. It is clear that the bearers of the YC practiced agriculture based on domesticated millets which are C 4 plants.…”
Section: Methodsmentioning
confidence: 99%
“…It is suggested that when the Cherepakha 13 site was occupied by the YC population, the level of the Sea of Japan dropped, and this may have caused a decrease of marine resources (Razjigaeva et al 2017a). Archaeobotanical research at the Cherepakha 13 site (Sergusheva and Moreva 2017) allowed us to identify the seeds of two species of millet: broomcorn millet ( Panicum miliaceum ) and foxtail millet ( Setaria italica ) in the YC layer. It is clear that the bearers of the YC practiced agriculture based on domesticated millets which are C 4 plants.…”
Section: Methodsmentioning
confidence: 99%